Pengaruh Belanja Modal Terhadap Pertumbuhan Kinerja Keuangan Daerah Dengan Pendapatan Asli Daerah Sebagai Variabel Intervening Padakabupaten / Kota Diprovinsi Jawa Tengahtahun 2013-2014 - Wardiani, Rina Eka; , Drs. Atwal Arifin, Ak.,M.Si (2017)
The research aims to examine the influence of the Capital Expenditure to the Local Financial Performance Growth trought Local Revenue as Intervening Variable in the cities and districts of Central Java Province in the local year 2013-2014. The population of this study is all of the cities and districts in Central Java Province that contain 42 samples by using purposive sampling as a sampling method. The data was used of this research is a secondary data from budget Realization Report of fiscal year 2013-2014. The finding shows that capital capital expenditure has influence to the local financial performance growth, however, the capital expenditure indirectly no influences to the local financial performance growth by throught the local revenue as intervening variable.